2021
DOI: 10.4103/ijo.ijo_1120_20
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations in renal allograft recipients

Abstract: Purpose: The aim of this study was to report the ocular findings in renal allograft recipients in India. Methods: A cross-sectional, comprehensive ophthalmic evaluation was performed, at least three months postrenal transplant, in 152 renal allograft recipients for the ocular findings. In addition, ocular findings were assessed for an association with the clinical variables like major etiologies of end-stage renal disease, pre-transplant dialysis duration, post-transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However they did not find any diabetic retinopathy (Berindán et al, 2017). Many literatures have mentioned various vision threatening retinal findings like central serous chorioretinopathy, epiretinal membrane, Central retinal vein occlusion, Retinal pigment epithelial detachment which were not present in our study population (Ginu et al, 2021;van Dijk et al, 2017 ).…”
Section: Discussionmentioning
confidence: 50%
“…However they did not find any diabetic retinopathy (Berindán et al, 2017). Many literatures have mentioned various vision threatening retinal findings like central serous chorioretinopathy, epiretinal membrane, Central retinal vein occlusion, Retinal pigment epithelial detachment which were not present in our study population (Ginu et al, 2021;van Dijk et al, 2017 ).…”
Section: Discussionmentioning
confidence: 50%
“… 8 On contrary, an Indian study has reported a much higher incidence (40%) of cataracts among patients with renal failure. 9 The mean use of steroids was 9.10±4.932 years ranging from 3 to 17 years, suggesting that the longer the duration of use of steroids more is the chances of cataract formation.…”
Section: Discussionmentioning
confidence: 97%
“…Ginu’s study accounted for only 11.2%, while the author’s study in the post-transplant population lasted from 0.3 to 14 years. 3 Sandhu’s study showed a post-transplant dry eye prevalence of 28% in subjects 3.3 ± 2.6 years after transplantation. 5 The difference in most dry eyes between our study and Ginu and Sandhu’s study may be due to factors, including patient populations, exam procedures, and methods used to assess dry eyes.…”
Section: Discussionmentioning
confidence: 98%
“…The explanation of the scaling difference from our study is due to the author’s classification criteria chosen by Keith Wagner Becker’s classification and the Early Treatment Diabetic Retinopathy Study (ETDRS). 3 Sandhu’s study found that the incidence of retinal lesions due to hypertension in patients after kidney transplantation was 40%, diabetic retinopathy was 12%, and other lesions accounted for 10%. Like the Ginu study, Sandhu uses Keith Wagner Becker’s retinal lesions classification system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation